Barriers and facilitators to uptake and persistence on prep among key populations in Southern Province, Zambia: a thematic analysis - Kirsten Stoebenau; Godfrey Muchanga; Sacha St-Onge Ahmad; Chiti Bwalya; Mwangala Mwale; Samara Toussaint; Choolwe Maambo; Carson J. Peters; Caitlin Baumhart; Linah K. Mwango; Marie-Claude C. Lavoie; Cassidy W. Claassen (BMC, 2024)
Abstract Background Especially in high HIV prevalence contexts, such as Zambia, effective biomedical prevention tools are needed for priority populations (PPs), including key populations (KPs), who are at higher risk. HIV pre-exposure prophylaxis (PrEP) has been scaled up nationally in Zambia, but little is known about barriers to PrEP use among specific PPs to date. Methods To understand barriers and facilitators to PrEP use in Zambia, we conducted a qualitative case study of PrEP services to PPs including sero-discordant couples (SDCs), female sex workers (FSWs), and men who have sex with men (MSM) in Livingstone. The study conducted in 2021 included in-depth interviews (n = 43) guided by the socio-ecological model, and focus group discussions (n = 4) with clinic and community-based providers and PrEP-eligible clients including users and non-users across PP groups. We used thematic analysis to analyze data using codes derived both deductively and inductively. Results We found multilevel barriers and facilitators to PrEP use. Cross-cutting barriers shared across PP groups included amplifying effects of PrEP being mistaken for antiretroviral drugs used to treat HIV, including anticipated stigma, and concerns about side-effects based on both misinformation and experience. In addition, stigmatized identities, particularly that of MSM, served as a barrier to PrEP use. The fear of being mislabeled as having HIV was of greatest concern for FSWs. Facilitators to PrEP use primarily included the importance of confidential, KP-sensitive services, and the role of informed, supportive family, friends, and peers. Participants across all PP groups urged expanded education efforts to increase awareness of PrEP within the general population toward mitigating concerns of being mislabeled as living with HIV. Conclusion To our knowledge, this is the first qualitative study of the PrEP cascade among multiple PPs in Zambia. This study provides important explanation for the low rates of PrEP continuation found in earlier demonstration trials among KPs in Zambia. The study also offers recommendations for programming efforts going forward such as inclusive PrEP awareness campaigns, expanded KP sensitivity training, and related efforts to thwart PrEP stigma while expanding access.